Evaluación del comportamiento agronómico de la nueva variedad de maíz chulpi (Zea Mays L.) INIAP 193 en el Campus Salache UTC 2021-2022. - Mopocita Cunalata, Nelson David (2023)
This research was conducted under the Maize Program at the National Institute of Agricultural Research (INIAP) in the Technical University of Cotopaxi - Salache, Eloy Alfaro, Canton Latacunga, Cotopaxi Province, Ecuador. The general objective was to evaluate the agronomic performance of the new corn variety chulpi (Zea mays L.) INIAP 193 at the SALACHE UTC 2021-2022 campus. To this end, activities were carried out to determine if the INIAP 193 chulpi variety adapts to the soil and climatic conditions of the Salache campus, to characterize morphologically the INIAP-193 chulpi maize variety and to establish production costs. For the data analysis, mean tables and graphs were made for the morphological variables: plant height, plant leaves number, ears number, ear height and days after flowering, quality variables are: ear type, grain type and ear coverage, post-harvest variables: weight at harvest in kg, dry matter, moisture percentage and yield per hectare, based on the folding No. 476 of INIAP-193 "Crocantito" improved Chulpi corn variety. With obtained data shows a good adaptation to the conditions determined by its morphological characterization with the Salache climatic conditions, since it complied with the parameters established in the corn cultivation guide for the Sierra region with a yield of 5.94 ton / Ha-1, in turn was characterized morphologically to the new variety corn chulpi INIAP 193, establishing production cost for the new variety released in the year 2022.